Prototipe Pengamatan Budidaya Aeroponik berbasis IoT (Internet of Things) - Yazid, Ihab; Ingetenta, Silas Octo; Yusro, Muhammad (LPPM Universitas Negeri Jakarta, 2020)
The purpose of this senior thesis designing the prototype observation cultivation aeroponik a planting land without the media. The method of planting aeroponik is very exact in urban areas , just need to the acquisition of land for minimal equipment and their some benefit from your water , with control the creation of the circulation of the round of rotary saving water. A method of this study using a method of research and development. Prototype observation cultivation aeroponik based a IoT uses software blynk and plx-daq. Tool making arranged in gradually: needs identification, needs analysis, hardware design grow box, design software and software Blynk PLX-DAQ, tool making, trouble shooting, and testing tools. Based on the results that prototype observation cultivation aeroponik based on the internet of things a lot of can work on what, chill control of the operating with a steady, and three sensor like; ultrasonic sensor can read the water level, censorship dht22 can inform temperature moisture, space and sensor ph analogous electrodes can calculate ph vitamin a-b. Mix. The testing using software blynk communication with the kind of serial on arduino ethernet. shieldsPlx-daq, can record and access to ms excel, ph data in full in accordance with expected. Penelitian ini bertujuan untuk merancang prototipe pengamatan budidaya Aeroponik sebuah penanaman tanpa media tanah. Metode penanaman aeroponik sangat tepat di wilayah perkotaan, hanya perlu lahan minim dan sedikit air, dengan mengontrol sirkulasi putaran air. Metode penelitian ini menggunakan metode penelitian dan pengembangan. Prototipe Pengamatan Budidaya Aeroponik berbasis IoT menggunakan software Blynk dan PLX-DAQ. Pembuatan alat disusun secara bertahap yaitu: Identifikasi kebutuhan, Analisis kebutuhan. Perancangan perangkat keras grow box, Perancangan perangkat lunak Blynk dan PLX-DAQ, Pembuatan alat, Trouble shooting, dan Pengujian alat. Berdasarkan hasil pengujian Prototipe Pengamatan Budidaya Aeroponik berbasis IoT dapat bekerja sesuai dengan apa yang dinginkan, dari rangkaian kendali yang beroperasi dengan stabil, dan tiga sensor seperti; sensor Ultrasonic dapat membaca ketinggian permukaan air, Sensor DHT22 dapat menginformasikan suhu kelembaban ruang, dan Sensor pH analog elektroda dapat menghitung pH vitamin A-B mix. Hasil pengujian menggunakan aplikasi Blynk sebagai komunikasi serial pada Arduino Ethernet Shields. PLX-DAQ dapat mendata, dan mengakses data pH ke MS Excel, secara maksimal sesuai dengan yang diharapkan.